Efficiency of the foreign currency options market - Hoque, Mohammed; Chan, Felix; Manzur, Meher (Elsevier BV, North-Holland, 2008)
This paper provides a new test of the efficiency of the currency option markets for four major cyrrencies -British Pound, Euro, Swiss Frank and Japanese Yen vis-a-vis the U.S. dollar. The approach is to simulate trading strategies to see if the well accepted no-arbitrage condition of put-call parity (PCP) holds in a trading environment. Augmented Dickey-Fuller and Philips-Perron test are used to check for the presence of unit root in the data, followed by a formal econometric analysis. The results indicate that the most currency option prices do not violate the PCP conditions, when transaction costs are allowed for.